Nilai-Nilai Cultural Dalam Tabu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Abstract. Culture encompasses a broad spectrum and its development shows certain shifts. Two main features of human are : value-systems and institutions whicil, especially in ancient societies, were both closely interconnected and integrated. The connection between the value-aspect and the institutional aspect in old societies is very obvious in taboo. The functions of taboo in traditional societies lay in their integrative and stabilizing forces in society. They functioned also as effective social controls. In tradisional societies, taboo expressed at the same time a strong cosmic-religiQus awareness. Obedience of society members towards taboo showed deep reverence towards God and the harmony of all life in the universe. With the development of society and the changes in culture, the quality of humeri life changed too, often taking place in revolutionary ways. Structural changes have their impact in value-systems, resulting in changes of outlook in humenkInd, for whom these changes are basic demands. Because of all these changes, taboo as a cultural institution soon lost its significance